Musculoskeletal work preceding the outward and inward Tkachev on uneven bars in artistic gymnastics - Kerwin, D. G.; Irwin, G. (Sports Biomechanics, 2010)
Outward facing Tkachevs on uneven bars have been the traditional technique employed by artistic gymnasts. Changes in bar spacing and judging have increased the popularity of the inward version of the skill, in which the gymnast faces towards the low bar as she straddles over the high bar. The purpose of this study was to compare these two variants of the women's Tkachev to examine the influence of the positioning of the low bar on the musculoskeletal demands placed on the gymnast. 3-D DLT reconstructed data sets from digitised video images of straddle Tkachevs performed at the 2000 Sydney Olympics were analysed. Five performances of each variant were compared using kinematics and inverse dynamics. Mean hip and shoulder kinematics were similar for both variants of the Tkachev, but for the inward, gymnasts released later, travelled higher and re-grasped earlier than for the outward. Hip joint moments were similar for both variants while shoulder moments were different. Total musculoskeletal demands were similar for both variants, although the distribution was markedly different with the shoulders contributing positively for the outward and negatively for the inward. Implications for training specificity, along with potential future developments for the inward variant, have been highlighted.